The evolution of the duckweed ionome mirrors losses in structural complexity - Smith, Kellie E; Zhou, Min; Flis, Paulina; Jones, Dylan H; Bishopp, Anthony; Yant, Levi (Annals of botany, 2024)
BACKGROUND AND AIMS: The duckweeds (Lemnaceae) consist of 36 species exhibiting impressive phenotypic variation, including the progressive evolutionary loss of a fundamental plant organ, the root. Loss of roots and reduction of vascular tissues in recently derived taxa occur in concert with genome expansions of ≤14-fold. Given the paired loss of roots and reduction in structural complexity in derived taxa, we focus on the evolution of the ionome (whole-plant elemental contents) in the context of these fundamental changes in body plan. We expect that progressive vestigiality and eventual loss of roots might have both adaptive and maladaptive consequences that are hitherto unknown. METHODS: We quantified the ionomes of 34 accessions in 21 species across all duckweed genera, spanning 70 Myr in this rapidly cycling plant (doubling times are as rapid as ~24 h). We related both micro- and macroevolutionary ionome contrasts to body plan remodelling and showed nimble microevolutionary shifts in elemental accumulation and exclusion in novel accessions. KEY RESULTS: We observed a robust directional trend in calcium and magnesium levels, decreasing from the ancestral representative Spirodela genus towards the derived rootless Wolffia, with the latter also accumulating cadmium. We also identified abundant within-species variation and hyperaccumulators of specific elements, with this extensive variation at the fine (as opposed to broad) scale. CONCLUSIONS: These data underscore the impact of root loss and reveal the very fine scale of microevolutionary variation in hyperaccumulation and exclusion of a wide range of elements. Broadly, they might point to trade-offs not well recognized in ionomes.
Keywords: Araceae; hořčík; biologická evoluce; evolution; Wolffia; duckweed; Wolffiella; vápník; ionomics; Biological Evolution; Plant Roots; kořeny rostlin; Calcium; ICP-MS; Lemna; Spirodela; fylogeneze; Magnesium; Vestigiality; Landoltia; Phylogeny